2013
DOI: 10.1186/2051-4190-23-11
|View full text |Cite
|
Sign up to set email alerts
|

“Breaking news” from spermatids

Abstract: During the haploid phase of spermatogenesis, spermatids undergo a complex remodeling of the paternal genome involving the finely orchestrated replacement of histones by the highly-basic protamines. The associated striking change in DNA topology is characterized by a transient surge of both single- and double-stranded DNA breaks in the whole population of spermatids which are repaired before spermiation. These transient DNA breaks are now considered part of the normal differentiation program of these cells. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Chromatin remodeling in spermatids is one of the most striking changes in nuclear architecture known to the eukaryotic world. This process is associated with transient DNA strand breakage that appears at mid‐spermiogenesis steps but becomes repaired during the final differentiation steps ensuring that no such DNA damage is transferred to the oocyte by the mature sperm [Laberge and Boissonneault, ; Leduc et al., ; Ward, ; Gouraud et al., ]. Chromatin remodeling and the transient surge in DNA strand breaks has been reported in human [Marcon and Boissonneault, ], mouse [Marcon and Boissonneault, ; Leduc et al., ], rat [Meyer‐Ficca et al., ], and drosophila [Rathke et al., ], as well as in the grasshopper [Cabrero et al., ] and in the algae [Wojtczak et al., ] pointing to a highly conserved mechanism with the potential to induce de novo genetic variation through subsequent generations [Grégoire et al., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin remodeling in spermatids is one of the most striking changes in nuclear architecture known to the eukaryotic world. This process is associated with transient DNA strand breakage that appears at mid‐spermiogenesis steps but becomes repaired during the final differentiation steps ensuring that no such DNA damage is transferred to the oocyte by the mature sperm [Laberge and Boissonneault, ; Leduc et al., ; Ward, ; Gouraud et al., ]. Chromatin remodeling and the transient surge in DNA strand breaks has been reported in human [Marcon and Boissonneault, ], mouse [Marcon and Boissonneault, ; Leduc et al., ], rat [Meyer‐Ficca et al., ], and drosophila [Rathke et al., ], as well as in the grasshopper [Cabrero et al., ] and in the algae [Wojtczak et al., ] pointing to a highly conserved mechanism with the potential to induce de novo genetic variation through subsequent generations [Grégoire et al., ].…”
Section: Discussionmentioning
confidence: 99%
“…DSBs are apparently part of the normal differentiation program of spermatids since these are observed in the whole population of these cells. DSBs may be induced either enzymatically by topoisomerases or nucleases and/or mechanically, as a result of increased torsional stress [Gouraud et al., ]. In any case, this indicates that the process may represent a window of genetic instability that can, in part, be responsible for the now well‐established male de novo mutation bias [Kong et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the number of mutations inherited by offspring is proportional to paternal age at the time of conception, supporting the hypothesis that the male germline mutation rate is directly correlated with the number of spermatogonial cell divisions34. In addition, there are several mechanistic factors, some of which are unique to males, that may contribute to germline specific mutation5: (a) male germ cells progressively lose DNA repair capacity as they advance through spermatogenesis67; (b) the chromatin remodeling required for the replacement of histone proteins with protamines during spermiogenesis8 may promote additional opportunities for misrepair of endogenous strand breaks9; (c) the process of meiosis provides opportunities to affect nucleotide composition that are unique to germ cells; and, (d) post-meiotic haploid germ cells cannot rely on sister chromatids as templates for homology-based repair mechanisms10. Thus, there are multiple mechanisms unique to male germ cells by which mutations can arise.…”
mentioning
confidence: 87%
“…Gouraud et al (2013) suggested that Spo11 has an additional function as a PM-DSB inducer based on microarray data (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE2736) showing that SPO11 transcription remains high in elongating spermatids in mice. Similarly, RT-PCR showed that SPO11 is transcribed from meiotic prophase (~3 hr) until the post-meiotic stage (6 hr) in Tetrahymena (Figure 6C), suggesting that Spo11 functions in post-meiotic processes.
10.7554/eLife.26176.012Figure 6.Spo11 is required for the correct execution of post-meiotic events.( A ) Acetic orcein staining of wild-type (top), ΔSPO11 (middle), and SPO11i (bottom) crosses.
…”
Section: Resultsmentioning
confidence: 99%